The Effectiveness of Village Fund Allocation Management in Improving the Development of Petak Village, Nuhon District, Banggai Regency - Hamsa Pakaji; Zulkifli Bokiu; Lukman Pakaya (International journal of technology and education research, 2026)
Village Fund Allocation (ADD) is an essential instrument in supporting village governance and promoting community development and empowerment. However, in practice, the effectiveness of ADD management still faces various challenges in terms of planning, implementation, and accountability. This study aims to analyze the effectiveness of Village Fund Allocation (ADD) management in enhancing the development of Petak Village, Nuhon Subdistrict, Banggai Regency, as well as to identify the supporting and inhibiting factors in its management. The research method employed is a qualitative method with a descriptive approach. Data collection techniques were conducted through interviews, observations, and documentation, with primary informants including village government officials and the community. Data analysis was performed through the stages of data reduction, data display, and conclusion drawing. The results indicate that the management of ADD in Petak Village covering the stages of planning, implementation, administration, reporting, and accountability has generally operated effectively and in accordance with applicable regulations. ADD contributes positively to village infrastructure development and community empowerment, although several obstacles remain, such as limited human resources, suboptimal community participation, and technical constraints in reporting.